Current Status of Oxide Fibre-Reinforced Oxide Ceramic Matrix Composites for Gas Turbine Applications - Kaya, Cengiz (TRANS TECH PUBLICATIONS LTD, 2010)
Recent developments in the processing, understanding and mechanical/thermomechanical properties of oxide fibre reinforced oxide ceramic matrix composites for high temperature applications are reported. Two dimensional composite plates and uni-directional tubular composite (so called mini-composite) specimens are successfully manufactured and their microstructure, matrix/ fiber interface as well as mechanical properties are examined. It is shown that the microstructural variations, such as porosity size and interface between fibre and matrix determine the fracture behaviour and high temperature performance of the composites. The optimised components produced are considered to be suitable for gas turbine applications.
Keywords: Oxide ceramic; Oxide fiber; Composite; Microstructure; CMCS; Materials Science